2013
DOI: 10.1111/2041-210x.12088
|View full text |Cite
|
Sign up to set email alerts
|

Modelling distributions of fossil sampling rates over time, space and taxa: assessment and implications for macroevolutionary studies

Abstract: Summary1. Observed patterns in the fossil record reflect not just macroevolutionary dynamics, but preservation patterns. Sampling rates themselves vary not simply over time or among major taxonomic groups, but within time intervals over geography and environment, and among species within clades. Large databases of presences of taxa in fossil-bearing collections allow us to quantify variation in per-collection sampling rates among species within a clade. We do this separately not just for different time/stratig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 59 publications
0
70
0
2
Order By: Relevance
“…Another limitation is that we do not have many of the traits available to neontologists to delimit species; therefore, fossil species have the potential to be both over-and under-split. Ideally, molecular phylogenetic approaches and modelling observed fossil ocurrences need to be integrated to make best use of data from both extant and extinct organisms [32,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is that we do not have many of the traits available to neontologists to delimit species; therefore, fossil species have the potential to be both over-and under-split. Ideally, molecular phylogenetic approaches and modelling observed fossil ocurrences need to be integrated to make best use of data from both extant and extinct organisms [32,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, Wagner & Marcot [45] recently found that within-interval recovery rates for fossil mammals are best described by lognormal, not uniform, distributions, indicating this assumption is likely to be violated. One way to potentially include such details in this framework is to hypothesize factors that strongly contribute to species preservation/sampling and incorporate these factors as covariates in CMR models.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most straightforward is to use databases to partition the data and develop per-locality sampling rate distributions that capture environmental, geographical and temporal variations in fossil recovery [5]. For example, Wagner & Marcot [5] calculated separate lognormal rates of recovery with the data binned by stage and continent, and using lepidosauromorphs (lizards, snakes, etc.) as a taphonomic/ecological control taxa for mammals, the subject of their study.…”
Section: Realistic Models Of Fossil Preservationmentioning
confidence: 99%
“…Likewise, partitioning the data by depositional environment may also yield improved results, but such an approach might be hindered by a lack of consistent environmental interpretations as well as problems of overpartitioning, leading to bins with insufficient data. Nonetheless, the approach of Wagner & Marcot [5] shows that considering environmental, geographic and temporal variations in sampling rate is superior to assuming uniform preservation.…”
Section: Realistic Models Of Fossil Preservationmentioning
confidence: 99%
See 1 more Smart Citation